The HIV/AIDS and youth in Croatia research project, 2005-2010 : an overview - Landripet, Ivan (2010)
A presentation of the main features of the repeated national study of sexuality-related knowledge, attitudes, beliefs and behaviors relevant in HIV prevention among youth, with an overview of the main results.